Addition of albumin to Traditional Risk Score Improved Prediction of Mortality in Individuals Undergoing Transcatheter Aortic Valve Replacement. Issue 11 (23rd September 2017) - Grossman, Yoni; Barbash, Israel M.; Fefer, Paul; Goldenberg, Ilan; Berkovitch, Anat; Regev, Ehud; Fink, Noam; Ben‐Zekry, Sagit; Brodov, Yafim; Kogan, Alexander; Guetta, Victor; Raanani, Ehud; et al.
Abstract : Objectives: The ability of the Society of Thoracic Surgeons (STS) and European System for Cardiac Operative Risk Evaluation (EuroSCORE)‐2 scores to predict outcomes after transcatheter aortic valve replacement (TAVR) is insufficient. Frailty and serum albumin as a frailty marker were shown to correlate with prognosis after TAVR. We sought to evaluate the additive value of serum albumin to STS and EuroSCORE‐2 scores to predict mortality in individuals undergoing TAVR. Design: Retrospective analysis. Setting: Tertiary‐care hospital prospective registry. Participants: Individuals who underwent TAVR (N = 426). Measurements: We compared survival rates according to median baseline albumin levels (4 g/dL), STS score (4.5%), and EuroSCORE‐2 (3.45%). Participants were divided into four groups according to median serum albumin and median STS and EuroSCORE‐2 scores (high vs low), and 1‐year survival rates were compared. A category‐free net reclassification index (NRI) was calculated to compare the ability of a model of STS or EuroSCORE‐2 alone to classify mortality risk with and without the addition of baseline serum albumin. Results: Participants with low albumin levels had higher mortality (hazard ratio (HR) = 3.03, 95% confidence interval (CI) = 1.66–5.26, P < .001). Participants with low serum albumin and a high STS (HR = 4.55, 95% CI = 2.21–9.38, P < .001) or EuroSCORE‐2 (HR = 2.72, 95% CI = 1.48–5.06, P = .001) score had higher mortality. Using NRI analysis, a model that included albumin in addition to STS correctly reclassified 42% of events (NRI = 0.58) and a model that included albumin in addition to EuroSCORE‐2 correctly reclassified 44% of events (NRI = 0.64). Conclusion: Serum albumin, as a marker of frailty, can significantly improve the ability of STS and EuroSCORE‐2 scores to predict TAVR‐related mortality.